Asymmetric fluoro-ether electrolyte suitable for extreme low temperature and preparation method of asymmetric fluoro-ether electrolyte
By using asymmetric fluorinated ether electrolytes in lithium batteries to form a stable SEI film, the problems of lithium dendrite growth and insufficient oxidation stability of ether electrolytes are solved, and high energy density and fast kinetic performance of lithium batteries at extremely low temperatures are achieved.
Patent Information
- Application Number
- CN202510842540.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-23
- Publication Date
- 2025-10-14
AI Technical Summary
Existing lithium metal batteries suffer from severe lithium dendrite growth at extremely low temperatures, resulting in battery instability. In addition, the ether electrolyte has insufficient oxidation stability and lithium salt solubility, which affects the battery's energy density and performance.
By using asymmetric fluorinated ether electrolytes and introducing asymmetric structures into the ether electrolytes, an anion-derived SEI film rich in inorganic components is formed, which improves the migration kinetics of lithium ions and matches high-voltage positive electrode materials.
Improve the stability and energy density of lithium batteries at extreme low temperatures, achieve fast lithium deposition/stripping kinetics, and be suitable for extreme low temperature environments.
Smart Images

Figure CN120784459A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery electrolytes, and in particular relates to an asymmetric fluoroether electrolyte suitable for extremely low temperatures and a preparation method thereof. Background Art
[0002] With the large-scale emergence and rapid development of wearable devices, portable electronic products and electric vehicles, higher requirements are placed on the energy density, cycle life, safety and reliability of energy storage devices. Unlike graphite anodes, lithium metal has a low reduction potential (-3.04V vs. SHE) and a theoretical specific capacity of up to 3860mAh g -1 Using it as the negative electrode is expected to achieve a battery energy density higher than 500Wh kg -1 However, lithium metal is highly chemically active and easily reacts with carbonate electrolytes. Furthermore, lithium undergoes significant volume changes during deposition and stripping, causing the SEI film on the lithium metal surface to rupture and then repair, resulting in an uneven SEI film. Uneven lithium deposition can lead to the formation of lithium dendrites, which reduces coulombic efficiency. Further growth of lithium dendrites can pierce the separator, causing safety issues such as battery short circuits. Furthermore, charge transfer kinetics are slower at low temperatures, further exacerbating uneven lithium deposition and making it more likely for lithium dendrites to grow.
[0003] Compared to ester electrolytes, ether electrolytes have better compatibility with lithium metal, a lower melting point, and maintain good performance even at low temperatures. However, ordinary ether molecules have poor oxidative stability and cannot be used in high-voltage cathode material systems. To improve the oxidative stability of ether electrolytes, fluorinated groups are introduced into the ether backbone, effectively lowering the molecular HOMO energy level and increasing the oxidative stability of the solvent molecules, thereby obtaining an electrolyte system compatible with high-voltage cathode materials. However, the introduction of fluorinated groups significantly reduces the solubility of ether molecules in lithium salts, thereby affecting the ionic conductivity of the electrolyte.
[0004] Therefore, how to improve the solubility of fluorinated ethers for lithium salts and thereby simultaneously improve the stability and energy density of lithium batteries is a technical problem that needs to be solved by the present invention. Summary of the Invention
[0005] To overcome the shortcomings of the aforementioned prior art, the present invention provides an asymmetric fluoroether electrolyte suitable for extreme low temperatures and a method for its preparation. By introducing an asymmetric structure into the ether electrolyte, the present invention significantly enhances the migration kinetics of lithium ions while maintaining the electrolyte's weak solvating ability and building an anion-derived, inorganic-rich SEI membrane. This optimizes the low-temperature performance of lithium metal batteries and enables compatibility with high-voltage cathode materials, thereby increasing the energy density of lithium metal batteries.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A first aspect of the present invention provides an asymmetric fluoroether electrolyte suitable for extreme low temperatures, wherein the asymmetric fluoroether electrolyte suitable for extreme low temperatures comprises: a lithium salt, a chain asymmetric fluoroether;
[0008] The structure of the chain asymmetric fluoroether is selected from any one or two of the general formulas (I) to (III):
[0009]
[0010] Preferably, the F x H 3-x In the fluorinated group of C, x is an integer in the range of 1 to 3, that is, the F x H 3-x The fluorinated group of C is any one of the following groups:
[0011] -----CF3-----CHF2-----CH2F.
[0012] Preferably, the chain asymmetric fluoroether is any one or two of the following molecular structures:
[0013]
[0014] Preferably, the lithium salt is at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium dioxalatoborate, lithium perchlorate, and lithium hexafluoroarsenate.
[0015] Preferably, the concentration of lithium salt in the asymmetric fluoroether electrolyte suitable for extremely low temperatures is 2 mol / L.
[0016] A second aspect of the present invention provides a method for preparing the above-mentioned asymmetric fluoroether electrolyte for extreme low temperatures, the preparation method comprising the following steps:
[0017] Step S1: Add the fluoroalcohol dropwise to a suspension of N,N-dimethylformamide and NaH in an ice bath, return the reaction to room temperature to generate sodium alkoxide, add iodomethane dropwise to the sodium alkoxide in an ice-water bath, return the reaction to room temperature after the addition is complete, add deionized water to quench the NaH, and purify to obtain an asymmetric fluoroether;
[0018] Step S2: pretreating the lithium salt, and then dissolving the lithium salt in any one or two asymmetric fluoroethers prepared in step S1 to obtain an asymmetric fluoroether electrolyte for extreme low temperatures.
[0019] Preferably, the fluoroalcohol includes any one of 2-fluoroethanol, 2,2-difluoroethanol, 2,2,2-trifluoroethanol, 3-fluoropropanol, 3,3-difluoropropanol, 3,3,3-trifluoropropanol, 4-fluoro-1-butanol, 4,4-difluoro-1-butanol, and 4,4,4-trifluoro-1-butanol.
[0020] Preferably, in step S1, the purification refers to obtaining a crude reaction product by distillation, washing the crude reaction product twice with a 1 mol / L NaOH solution, a saturated NaCl solution, and a 1 mol / L HCl solution in sequence, retaining the organic phase after each washing, and then drying with anhydrous sodium sulfate, filtering, and distilling to obtain the product.
[0021] Preferably, in step S1, the molar ratio of the fluoroalcohol, NaH, and iodomethane is 1:1.5:1.2.
[0022] The third aspect of the present invention provides an application of the above-mentioned asymmetric fluoroether electrolyte for extreme low temperatures in a lithium battery. The lithium battery is composed of a positive electrode, a negative electrode, a separator and the above-mentioned asymmetric fluoroether electrolyte for extreme low temperatures to form a sealed lithium battery.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention obtains an asymmetric fluoroether lithium battery electrolyte suitable for extreme low temperature environments through reasonable molecular design. The fluoroalkyl group on one side of the ether bond can improve the antioxidant properties of the solvent and weaken the solvation ability, forming an SEI film rich in inorganic components such as LiF during the battery charge and discharge process, thereby improving the stability of the battery. A methyl group is introduced on the other side of the ether bond to improve the ability to dissolve lithium salts. The reasonable design of this asymmetric fluoroether electrolyte can significantly improve the reduction reversibility and kinetics of lithium, obtain an electrolyte system suitable for extreme low temperature environments and resistant to high voltage, and effectively promote the development of lithium batteries with high energy density and stable operation at extreme low temperatures. At the same time, the preparation method and process of the present invention are simple, safe to operate and have high purity, and are suitable for industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of compound 8 in Example 1.
[0026] Figure 2 is the carbon NMR spectrum of compound 8 in Example 1.
[0027] Figure 3 is the hydrogen nuclear magnetic resonance spectrum of compound 9 in Example 3.
[0028] Figure 4 is the carbon NMR spectrum of compound 9 in Example 3.
[0029] Figure 5 This is the hydrogen nuclear magnetic resonance spectrum of compound 7 in Example 4.
[0030] Figure 6 It is the carbon NMR spectrum of compound 7 in Example 4.
[0031] Figure 7 This is a performance diagram of the Cu||Li battery in Example 1 assembled with 2M LiFSI in TFPM electrolyte.
[0032] Figure 8 19 mg cm in Example 1 -2 Battery performance diagram of NMC811||50μm Li battery assembled with 2M LiFSI in TFPM electrolyte.
[0033] Figure 9 This is a battery performance diagram of a Cu||Li battery assembled with 2M LiFSI in TFPM electrolyte at a low temperature of -40°C in Example 1.
[0034] Figure 10 In Example 1, under the condition of low temperature -40°C, LiNi 0.90 Co 0.05 Mn 0.05 Battery performance diagram of O2(NCM9055)||Li soft-pack battery assembled with 2M LiFSI in TFPM electrolyte.
[0035] Figure 11 3.5 mg cm in Example 2 -2 Battery performance diagram of NMC811||Li battery assembled with 2M LiFSI in DFEM / TFPM 2:8byvol electrolyte.
[0036] Figure 12 This is a battery performance diagram of a Cu||Li battery assembled with 2M LiFSI in DFEM / TFPM 2:8 by vol electrolyte at a low temperature of -60°C in Example 2.
[0037] Figure 13 In Example 2, at a low temperature of -60°C, 3.5 mg cm -2 Battery performance diagram of NMC811||Li battery assembled with 2MLiFSI in DFEM / TFPM 2:8 by vol electrolyte.
[0038] Figure 14 3.5 mg cm in Example 3 -2Battery performance diagram of NMC811||Li battery assembled with 2M LiFSI in TFBM electrolyte.
[0039] Figure 15 This is a battery performance diagram of a Cu||Li battery assembled with 2M LiFSI in TFBM electrolyte at a low temperature of -40°C in Example 3.
[0040] Figure 16 In Example 4, at a low temperature of -40 °C, 3.5 mg cm -2 Battery performance diagram of NMC811||Li battery assembled with 2MLiFSI in TFEM-TFBM 2:8 by vol electrolyte.
[0041] Figure 17 This is a battery performance diagram of a Cu||Li battery assembled with 2M LiFSI in TFEM-TFBM 2:8 by vol electrolyte at a low temperature of -60°C in Example 4.
[0042] Figure 18 In Example 4, at a low temperature of -60°C, 3.5 mg cm -2 Battery performance diagram of NMC811||Li battery assembled with 2MLiFSI in TFEM-TFBM 2:8 by vol electrolyte.
[0043] Figure 19 In Example 5, at a low temperature of -40 °C, 19 mg cm -2 Battery performance diagram of NMC811||50μm Li battery assembled with 2MLiFSI in FPM-TFPM 4:6 by vol electrolyte.
[0044] Figure 20 In Example 6, at a low temperature of -40 °C, 3.5 mg cm -2 Battery performance diagram of NMC811||Li battery assembled with 2MLiFSI in DFBM-TFBM 3:7 by vol electrolyte. DETAILED DESCRIPTION
[0045] The following is a further description of specific embodiments of the present invention. It should be noted that the description of these embodiments is intended to facilitate understanding of the present invention and does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below may be combined with each other as long as they do not conflict with each other.
[0046] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0047] Preparation and assembly of electrodes and batteries:
[0048] Ternary cathode material LiNi 0.8 Co 0.1 Mn 0.1 Preparation of O2 (NCM811) electrode: NCM811, acetylene black, and PVDF binder were mixed in a ratio of 80:12:8 and dispersed into a slurry using N-methylpyrrolidone (NMP) solution. The slurry was evenly coated on aluminum foil using a 120 μm scraper and then vacuum-dried at 120 °C for 12 h. The slurry was sliced into a 12 mm diameter with an active material loading of approximately 3.5 mg cm-3. -2 The electrode discs were placed in a glove box for later use;
[0049] NCM811, acetylene black, and PVDF binder were mixed in a ratio of 80:12:8 and dispersed into a slurry using N-methylpyrrolidone (NMP) solution. The slurry was evenly coated on aluminum foil using a 1000 μm scraper and then vacuum-dried at 120 °C for 12 h. The slurry was sliced into a 12 mm diameter with an active material loading of approximately 19 mg cm using a microtome. -2 The electrode discs were placed in a glove box for later use;
[0050] Preparation of Cu||Li and NCM811||Li batteries: In a glove box, cells were assembled using Cu and the prepared electrode sheet as the positive electrode, lithium metal as the negative electrode, and Celgard 2500 as the separator. Cu||Li and NCM811||Li cells were assembled using the different electrolytes prepared in the following examples, and their electrochemical performance was tested at room temperature, -40°C, and -60°C.
[0051] Example 1: Preparation and testing of 2M LiFSI in TFPM, an asymmetric fluoroether electrolyte suitable for extreme low temperatures
[0052] Step S1: 25 g of 3,3,3-trifluoropropanol was slowly added dropwise into a suspension of anhydrous N,N-dimethylformamide (DMF) and 1.5 eq of NaH under ice water bath condition, then the reaction was allowed to recover to room temperature for 1 h. 1.2 eq of methyl iodide (MeI) was slowly added dropwise under ice water bath, and the reaction was allowed to recover to room temperature for 16 h. After the reaction was completed, the NaH was quenched with a small amount of deionized water, and the crude product of the reaction was obtained by distillation. The crude product of the reaction was washed with 1 mol / L NaOH solution, saturated NaCl solution and 1 mol / L HCl solution in turn, and the organic phase was retained after each washing. Then it was dried with anhydrous sodium sulfate, filtered and distilled to obtain 3,3,3-trifluoro-1-propyl methyl ether (compound 8). The prepared compound 8 was placed in a glove box with water content and oxygen content less than 0.01 ppm at 25°C, dried with molecular sieves to remove water, Figure 1 is the nuclear magnetic resonance hydrogen spectrum of compound 8; Figure 2 is the nuclear magnetic resonance carbon spectrum of compound 8, from Figure 1 and Figure 2 It can be seen that the synthesis of 3,3,3-trifluoro-1-propyl methyl ether is successful.
[0053] Step S2: 374.14 mg of lithium bisfluorosulfonylimide (LiFSI) was weighed into a 1.0 ml solution of 3,3,3-trifluoro-1-propyl methyl ether and stirred overnight in a glove box with water content and oxygen content less than 0.01 ppm at 25°C, so as to be fully dissolved and uniformly mixed, to prepare a lithium bisfluorosulfonylimide / 3,3,3-trifluoro-1-propyl methyl ether electrolyte with a concentration of 2 mol / L (denoted as 2M LiFSI in TFPM).
[0054] As Figure 7 is the battery performance chart of Cu||Li battery assembled with electrolyte of 2M LiFSI in TFPM. It can be seen from the chart that the battery using electrolyte of 2M LiFSI in TFPM can be stably operated for more than 850 cycles with an average coulombic efficiency of 99.3%.
[0055] As Figure 8 is the 19 mg cm -2 is the battery performance chart of NMC811||50 pm Li battery assembled with electrolyte of 2M LiFSI in TFPM. It can be seen from the chart that even in the harsh conditions of poor lithium and high load NMC811, the battery assembled with electrolyte of 2M LiFSI in TFPM can be stably operated for more than 200 cycles at 30°C under the condition of 0.2C charging / 0.5C discharging, with a capacity retention rate of 93.7% and an average coulombic efficiency of 99.8%.
[0056] As Figure 9The figure shows the performance of a Cu||Li battery assembled with 2M LiFSI in TFPM electrolyte at -40°C. As can be seen from the figure, the battery using 2M LiFSI in TFPM electrolyte can still achieve a charge of 1.0 mA cm even in a low temperature environment of -40°C. -2 Lithium deposition / stripping is performed at a high current density with a Coulombic efficiency of up to 98.7%.
[0057] like Figure 10 At low temperature -40℃, LiNi 0.90 Co 0.05 Mn 0.05 The performance diagram of the O2 (NCM9055) || Li soft pack battery assembled with 2M LiFSI in TFPM electrolyte. As can be seen from the figure, the soft pack battery using 2M LiFSI in TFPM electrolyte has a discharge capacity of 6.3Ah when activated at a rate of 0.1C at room temperature. Based on the overall weight of the battery and the battery discharge medium voltage, the energy density of the soft pack battery is as high as 483Wh kg -1 When the battery was cycled at -40°C, its first-cycle discharge capacity reached 4.40Ah, maintaining 70% of its room temperature capacity, and its energy density reached 341.1Wh kg -1 The soft-pack battery has a capacity retention rate of 90.8% after 40 cycles.
[0058] Example 2: Preparation and testing of 2M LiFSI in DFEM / TFPM 2:8 by volume asymmetric fluoroether electrolyte for extreme low temperature
[0059] Step S1: Under ice-water bath conditions, 25g of 2,2-difluoroethanol was slowly added dropwise to anhydrous N,N-dimethylformamide (DMF) and 1.5eq of NaH suspension, and then the reaction was returned to room temperature for 1h. Under ice-water bath conditions, 1.2eq of iodomethane (MeI) was slowly added dropwise, and the reaction system was reacted at room temperature for 16h. After the reaction was completed, the NaH was quenched with a small amount of deionized water, and the crude reaction product was obtained by distillation. The crude reaction product was washed twice with 1mol / L NaOH solution, saturated NaCl solution, and 1mol / L HCl solution in sequence, retaining the organic phase after each wash. It was then dried over anhydrous sodium sulfate, filtered, and distilled to obtain 2,2-difluoro-1-ethyl methyl ether (Compound 4). Under ice-water bath conditions, 25g of 3,3,3-trifluoropropanol was slowly added dropwise to anhydrous N,N-dimethylformamide (DMF) and 1.5eq of NaH suspension, and then the reaction was returned to room temperature for 1h. 1.2 eq of iodomethane (MeI) was slowly added dropwise under an ice-water bath, and the reaction system was reacted at room temperature for 16 h. After completion of the reaction, NaH was quenched with a small amount of deionized water, and a crude reaction product was obtained by distillation. The crude reaction product was washed twice with 1 mol / L NaOH solution, saturated NaCl solution, and 1 mol / L HCl solution in sequence, and the organic phase was retained after each washing. It was then dried over anhydrous sodium sulfate, filtered, and distilled to obtain 3,3,3-trifluoro-1-propyl methyl ether (Compound 8). The prepared Compound 4 and Compound 8 were placed in a glove box at 25 ° C with a water content and an oxygen content of less than 0.01 ppm, dried over molecular sieves, and moisture was removed.
[0060] Step S2: At 25 ° C., in a glove box with a water content and oxygen content of less than 0.01 ppm, 374.14 mg of lithium bis(fluorosulfonyl)imide (LiFSI) was weighed and dissolved in a mixed solution of 0.2 ml of 2,2-difluoro-1-ethyl methyl ether and 0.8 ml of 3,3,3-trifluoro-1-propyl methyl ether, and stirred overnight to fully dissolve and mix evenly to obtain lithium bis(fluorosulfonyl)imide / 2,2-difluoro-1-ethyl methyl ether / 3,3,3-trifluoro-1-propyl methyl ether with a concentration of 2 mol / L (denoted as 2M LiFSI in DFEM / TFPM 2:8 by vol).
[0061] like Figure 11 3.5 mg cm -2 Performance of an NMC811||Li battery assembled with a 2M LiFSI in DFEM / TFPM 2:8 by vol electrolyte. The figure shows that under high-rate charge and discharge conditions of 5C, the battery using 2M LiFSI in DFEM / TFPM 2:8 by vol electrolyte can stably cycle 900 times at 30°C with an average coulombic efficiency exceeding 99.9%.
[0062] like Figure 12 The figure shows the performance of a Cu||Li battery assembled with 2M LiFSI in DFEM / TFPM 2:8 by vol electrolyte at -60°C. As can be seen from the figure, the battery using 2M LiFSI in DFEM / TFPM 2:8 by vol electrolyte can still achieve a charge flow rate of 0.1 mA cm at an extremely low temperature of -60°C. -2 Lithium deposition / stripping was carried out at a current density of 100 nm and a Coulombic efficiency of 96.1%.
[0063] like Figure 13 At -60°C, 3.5 mg cm -2 Performance of an NMC811||Li battery assembled with a 2M LiFSI in DFEM / TFPM 2:8 by vol electrolyte. The figure shows that at -60°C, the battery assembled with 2M LiFSI in DFEM / TFPM 2:8 by vol electrolyte can achieve 150 stable cycles at a rate of 0.05C.
[0064] Example 3: Preparation and testing of 2M LiFSI in TFBM, an asymmetric fluoroether electrolyte for extreme low temperature applications
[0065] Step S1: Under ice-water bath conditions, 25g of 4,4,4-trifluoro-1-butanol was slowly added dropwise to anhydrous N,N-dimethylformamide (DMF) and 1.5eq of NaH suspension, and then the reaction was restored to room temperature for 1h. 1.2eq of iodomethane (MeI) was slowly added dropwise under ice-water bath, and the reaction system was reacted at room temperature for 16h. After the reaction was completed, NaH was quenched with a small amount of deionized water, and the crude reaction product was obtained by distillation. The crude reaction product was washed twice with 1mol / L NaOH solution, saturated NaCl solution and 1mol / L HCl solution in sequence, and the organic phase was retained after each washing. It was then dried with anhydrous sodium sulfate, filtered and distilled to obtain 4,4,4-trifluoro-1-butyl methyl ether (Compound 9). The prepared Compound 9 was placed in a glove box at 25°C with a water content and an oxygen content of less than 0.01ppm, dried over molecular sieves, and moisture was removed. Figure 3 is the H NMR spectrum of compound 9. Figure 4 is the C NMR spectrum of compound 9, from Figure 3 and Figure 4 It can be seen that 4,4,4-trifluoro-1-butyl methyl ether was successfully synthesized.
[0066] Step S2: At 25°C in a glove box with a water content and oxygen content of less than 0.01 ppm, 374.14 mg of lithium bis(fluorosulfonyl)imide (LiFSI) was weighed and dissolved in a mixed solution of 1.0 ml of 4,4,4-trifluoro-1-butyl methyl ether and stirred overnight to fully dissolve and mix evenly to obtain a lithium bis(fluorosulfonyl)imide / 4,4,4-trifluoro-1-butyl methyl ether electrolyte with a concentration of 2 mol / L (denoted as 2M LiFSI in TFBM).
[0067] like Figure 14 3.5 mg cm -2 Performance diagram of an NMC811||Li battery assembled with a 2M LiFSI in TFBM electrolyte. As shown in the figure, under 5C high-rate charge and discharge conditions, the battery using 2M LiFSI in TFBM electrolyte can also cycle stably at a high rate of 5C at 30°C.
[0068] like Figure 15 The performance of the Cu||Li battery assembled with 2M LiFSI in TFBM electrolyte at -40°C is shown in the figure. As can be seen from the figure, the battery assembled with 2M LiFSI in TFBM electrolyte has a high capacitance at 1.0mA cm -2 At high current density, its coulombic efficiency can reach 97.0%.
[0069] Example 4: Preparation and testing of 2M LiFSI in TFEM-TFBM 2:8 by volume asymmetric fluoroether electrolyte for extreme low temperature applications
[0070] Step S1: In an ice-water bath, 25 g of 2,2,2-trifluoroethanol was slowly added dropwise to a suspension of anhydrous N,N-dimethylformamide (DMF) and 1.5 eq of NaH, and the mixture was allowed to react at room temperature for 1 h. In an ice-water bath, 1.2 eq of iodomethane (MeI) was slowly added dropwise, and the reaction system was allowed to react at room temperature for 16 h. After completion of the reaction, the NaH was quenched with a small amount of deionized water, and a crude reaction product was obtained by distillation. The crude reaction product was washed twice with 1 mol / L NaOH solution, saturated NaCl solution, and 1 mol / L HCl solution, respectively, retaining the organic phase after each wash. It was then dried over anhydrous sodium sulfate, filtered, and distilled to obtain 2,2,2-trifluoro-1-ethyl methyl ether (Compound 7). In an ice-water bath, 25 g of 4,4,4-trifluoro-1-butanol was slowly added dropwise to a suspension of anhydrous N,N-dimethylformamide (DMF) and 1.5 eq of NaH, and the mixture was allowed to react at room temperature for 1 h. 1.2eq of iodomethane (MeI) was slowly added dropwise under an ice-water bath, and the reaction system was reacted at room temperature for 16h. After the reaction was completed, NaH was quenched with a small amount of deionized water, and the crude reaction product was obtained by distillation. The crude reaction product was washed twice with 1mol / L NaOH solution, saturated NaCl solution and 1mol / L HCl solution in sequence, and the organic phase was retained after each washing. It was then dried with anhydrous sodium sulfate, filtered and distilled to obtain 4,4,4-trifluoro-1-butyl methyl ether (Compound 9). The prepared Compound 7 and Compound 9 were placed in a glove box at 25°C with a water content and an oxygen content of less than 0.01ppm, dried over molecular sieves, and moisture was removed. Figure 5 is the H NMR spectrum of compound 7. Figure 6 is the C NMR spectrum of compound 7, Figure 5 and Figure 6 It can be seen that 2,2,2-trifluoro-1-ethyl methyl ether was successfully synthesized.
[0071] Step S2: At 25 ° C., in a glove box with a water content and oxygen content of less than 0.01 ppm, 374.14 mg of lithium bis(fluorosulfonyl)imide (LiFSI) was weighed and dissolved in a mixed solution of 0.2 ml of 2,2,2-trifluoro-1-ethyl methyl ether and 0.8 ml of 4,4,4-trifluoro-1-butyl methyl ether, and stirred overnight to fully dissolve and mix evenly to prepare a 2 mol / L lithium bis(fluorosulfonyl)imide / 2,2,2-trifluoro-1-ethyl methyl ether / 4,4,4-trifluoro-1-butyl methyl ether electrolyte (denoted as 2M LiFSI inTFEM-TFBM 2:8 by vol).
[0072] like Figure 16 At -40°C, 3.5 mg cm -2Performance of an NMC811||Li battery assembled with an electrolyte of 2M LiFSI in TFEM-TFBM 2:8 by vol. The figure shows that at -40°C, the battery assembled with 2M LiFSI in TFEM-TFBM 2:8 by vol can operate stably at a rate of 0.2C for over 500 cycles.
[0073] like Figure 17 The figure shows the performance of a Cu||Li battery assembled with 2M LiFSI in TFEM-TFBM 2:8 by vol electrolyte at -60°C. As can be seen from the figure, the battery using 2M LiFSI in TFEM-TFBM 2:8 by vol electrolyte can still achieve a charge of 0.1 mA cm at an extremely low temperature of -60°C. -2 Lithium deposition / stripping was performed at a current density of 1.5 Å, with a Coulombic efficiency of 91.7%.
[0074] like Figure 18 At -60°C, 3.5 mg cm -2 Performance of an NMC811||Li battery assembled with an electrolyte of 2M LiFSI in TFEM-TFBM 2:8 by vol. As shown in the figure, at a low temperature of -60°C, the battery assembled with an electrolyte of 2M LiFSI in TFEM-TFBM 2:8 by vol can achieve 100 stable cycles at a rate of 0.1C.
[0075] Example 5: Preparation and testing of 2M LiFSI in FPM-TFPM 4:6 by volume asymmetric fluoroether electrolyte for extreme low temperature applications
[0076] Step S1 : 25 g of 3-fluoropropanol was slowly added dropwise to a suspension of anhydrous N,N-dimethylformamide (DMF) and 1.5 eq of NaH under ice water bath condition, then the reaction was allowed to recover to room temperature for 1 h. 1.2 eq of methyl iodide (MeI) was slowly added dropwise under ice water bath, and the reaction was allowed to recover to room temperature for 16 h. After the reaction was completed, the NaH was quenched with a small amount of deionized water, and the crude product of the reaction was obtained by distillation. The crude product of the reaction was washed with 1 mol / L NaOH solution, saturated NaCl solution and 1 mol / L HC1 solution in sequence, and the organic phase was retained after each washing. Then it was dried with anhydrous sodium sulfate, filtered and distilled to obtain 3-fluoro-1-propyl methyl ether (compound 2). 25 g of 3,3,3-trifluoropropanol was slowly added dropwise to a suspension of anhydrous N,N-dimethylformamide (DMF) and 1.5 eq of NaH under ice water bath condition, then the reaction was allowed to recover to room temperature for 1 h. 1.2 eq of methyl iodide (MeI) was slowly added dropwise under ice water bath, and the reaction was allowed to recover to room temperature for 16 h. After the reaction was completed, the NaH was quenched with a small amount of deionized water, and the crude product of the reaction was obtained by distillation. The crude product of the reaction was washed with 1 mol / L NaOH solution, saturated NaCl solution and 1 mol / L HC1 solution in sequence, and the organic phase was retained after each washing. Then it was dried with anhydrous sodium sulfate, filtered and distilled to obtain 3,3,3-trifluoro-1-propyl methyl ether (compound 8). The prepared compound 2 and compound 8 were placed in a glove box at 25 °C with water content and oxygen content less than 0.01 ppm, dried with molecular sieves to remove water.
[0077] Step S2: 374.14 mg of lithium bisfluorosulfonylimide (LiFSI) was weighed in a glove box at 25 °C with water content and oxygen content less than 0.01 ppm, dissolved in a mixed solution of 0.4 ml of 3-fluoro-1-propyl methyl ether and 0.6 ml of 3,3,3-trifluoro-1-propyl methyl ether, stirred overnight to make a lithium bisfluorosulfonylimide / 3-fluoro-1-propyl methyl ether / 3,3,3-trifluoro-1-propyl methyl ether electrolyte with a concentration of 2 mol / L (denoted as 2M LiFSI in FPM-TFPM 4:6 by vol).
[0078] As Figure 19 To be at low temperature -40 °C, 19 mg cm -2Battery performance plot of NMC811 || 50 pm Li battery assembled with electrolyte of 2M LiFSI in FPM-TFPM 4:6 by vol. From the plot, it can be seen that even in the harsh condition of poor lithium, high load NMC811, the battery assembled with electrolyte of 2M LiFSI in FPM-TFPM 4:6 by vol can still run stably at a rate of 0.1C for more than 200 cycles at low temperature -40°C, the capacity retention reaches 94.1%, and the average coulombic efficiency is as high as 99.9%.
[0079] Example 6: Preparation and testing of asymmetric fluoro-ether electrolyte 2M LiFSI in DFBM-TFBM 3:7 by vol for extreme low temperature
[0080] Step S1 : 25 g of 4,4-difluoro-1-butanol was slowly added dropwise to anhydrous N,N-dimethylformamide (DMF) and 1.5 eq of NaH suspension under ice water bath condition, and then the reaction was carried out at room temperature for 1 h. 1.2 eq of methyl iodide (MeI) was slowly added dropwise under ice water bath, and the reaction system was reacted at room temperature for 16 h. After the reaction was completed, NaH was quenched with a small amount of deionized water, and the reaction crude product was obtained by distillation. The reaction crude product was washed with 1 mol / L NaOH solution, saturated NaCl solution and 1 mol / L HCl solution in turn, and the organic phase was retained after each washing. Then it was dried with anhydrous sodium sulfate, filtered and distilled to obtain 4,4-difluoro-1-butyl methyl ether (compound 6). 25 g of 4,4,4-trifluoro-1-butanol was slowly added dropwise to anhydrous N,N-dimethylformamide (DMF) and 1.5 eq of NaH suspension under ice water bath condition, and then the reaction was carried out at room temperature for 1 h. 1.2 eq of methyl iodide (MeI) was slowly added dropwise under ice water bath, and the reaction system was reacted at room temperature for 16 h. After the reaction was completed, NaH was quenched with a small amount of deionized water, and the reaction crude product was obtained by distillation. The reaction crude product was washed with 1 mol / L NaOH solution, saturated NaCl solution and 1 mol / L HCl solution in turn, and the organic phase was retained after each washing. Then it was dried with anhydrous sodium sulfate, filtered and distilled to obtain 4,4,4-trifluoro-1-butyl methyl ether (compound 9). The prepared compound 6 and compound 9 were placed in a glove box at 25°C with water content and oxygen content less than 0.01 ppm, dried with molecular sieves to remove water.
[0081] Step S2: At 25 ° C., in a glove box with a water content and oxygen content of less than 0.01 ppm, 374.14 mg of lithium bis(fluorosulfonyl)imide (LiFSI) was weighed and dissolved in a mixed solution of 0.3 ml of 4,4-difluoro-1-butyl methyl ether and 0.7 ml of 4,4,4-trifluoro-1-butyl methyl ether, and stirred overnight to fully dissolve and mix evenly to prepare a 2 mol / L lithium bis(fluorosulfonyl)imide / 4,4-difluoro-1-butyl methyl ether / 4,4,4-trifluoro-1-butyl methyl ether electrolyte (denoted as 2M LiFSI in DFBM-TFBM 3:7 by vol).
[0082] like Figure 20 At -40°C, 3.5 mg cm -2 Performance of an NMC811||Li battery assembled with a 2M LiFSI in DFBM-TFBM 3:7 by vol electrolyte. The figure shows that at -40°C, the battery assembled with a 2M LiFSI in DFBM-TFBM 3:7 by vol electrolyte can operate stably at a rate of 0.2C for over 500 cycles.
[0083] The results of the above examples demonstrate that electrolytes containing the asymmetric fluoroether molecules of the present invention exhibit excellent film-forming properties on lithium metal surfaces, enabling long-term cycling of lithium metal batteries. These electrolytes can also be used in applications requiring high-rate charge and discharge (e.g., drone lifts). In low-temperature environments, electrolytes containing the asymmetric fluoroether molecules of the present invention can maintain rapid lithium kinetics and reversibility, demonstrating excellent extreme low-temperature practicality and potential application in extreme low-temperature environments such as space, polar regions, and the deep sea.
[0084] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. It is apparent to those skilled in the art that various changes, modifications, substitutions, and variations of these embodiments may be made without departing from the principles and spirit of the present invention, and the changes still fall within the scope of protection of the present invention.
Claims
1. An asymmetric fluoroether electrolyte suitable for extremely low temperatures, characterized in that: The asymmetric fluoroether electrolyte suitable for extremely low temperatures comprises: lithium salt, chain asymmetric fluoroether; The structure of the chain asymmetric fluoroether is selected from any one or two of the general formulas (I) to (III):
2. The asymmetric fluoroether electrolyte suitable for extreme low temperatures according to claim 1, characterized in that: The F x H 3-x In the fluorinated group of C, x is an integer in the range of 1 to 3, that is, the F x H 3-x The fluorinated group of C is any one of the following groups:
3. The asymmetric fluoroether electrolyte suitable for extreme low temperatures according to claim 2, characterized in that: The chain asymmetric fluoroether is any one or two of the following molecular structures:
4. The asymmetric fluoroether electrolyte suitable for extreme low temperatures according to claim 1, characterized in that: The lithium salt is at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium dioxalatoborate, lithium perchlorate, and lithium hexafluoroarsenate.
5. The asymmetric fluoroether electrolyte suitable for extreme low temperatures according to claim 1, characterized in that: The concentration of lithium salt in the asymmetric fluoroether electrolyte suitable for extremely low temperatures is 2 mol / L.
6. A method for preparing an asymmetric fluoroether electrolyte for extreme low temperature according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Step S1: Add the fluoroalcohol dropwise to a suspension of N,N-dimethylformamide and NaH in an ice bath, return the reaction to room temperature to generate sodium alkoxide, add iodomethane dropwise to the sodium alkoxide in an ice-water bath, return the reaction to room temperature after the addition is complete, add deionized water to quench the NaH, and purify to obtain an asymmetric fluoroether; Step S2: pretreating the lithium salt, and then dissolving the lithium salt in any one or two asymmetric fluoroethers prepared in step S1 to obtain an asymmetric fluoroether electrolyte for extreme low temperatures.
7. The method for preparing an asymmetric fluoroether electrolyte for extreme low temperature according to claim 6, characterized in that: The fluoroalcohol includes any one of 2-fluoroethanol, 2,2-difluoroethanol, 2,2,2-trifluoroethanol, 3-fluoropropanol, 3,3-difluoropropanol, 3,3,3-trifluoropropanol, 4-fluoro-1-butanol, 4,4-difluoro-1-butanol and 4,4,4-trifluoro-1-butanol.
8. The method for preparing an asymmetric fluoroether electrolyte for extreme low temperature according to claim 6, characterized in that: In step S1, the purification refers to obtaining a crude reaction product by distillation, washing the crude reaction product twice with a 1 mol / L NaOH solution, a saturated NaCl solution, and a 1 mol / L HCl solution in sequence, retaining the organic phase after each washing, and then drying it with anhydrous sodium sulfate, filtering, and distilling to obtain the product.
9. The method for preparing an asymmetric fluoroether electrolyte for extreme low temperature according to claim 6, characterized in that: In step S1, the molar ratio of the fluoroalcohol, NaH, and iodomethane is 1:1.5:1.
2.
10. Use of the asymmetric fluoroether electrolyte for extreme low temperature according to any one of claims 1 to 5 in a lithium battery.